Developing Picture Story Book Media to Teach Speaking Skills in Kindergarten - Ati Chairi Larasati; Farida Nugrahani; Benedictus Sudiyana (Universitas Negeri Makassar, 2023)
Engaging media is necessary to stimulate children's speaking skills in kindergarten. The purpose of this study is (1) to describe the development of media big book picturesque stories for learning speech skills in children's kindergarten, (2) to describe the feasibility, practicality, and effectiveness of big book picturesque media for learning kindergarten speech skills. This research employed the research and development of Borg and Gall, which, due to time and cost limitations, then took only seven stages—data collection techniques using questionnaires and observations. Data is validated with media validity assessment by material experts and media experts—data analysis techniques using quantitative and qualitative data analysis. Design development plans using flowcharts, define access learning objectives, formulate indicators references, define media titles, compile storytelling, layout Big Book story images, create storyboards, and create validation lifts. Results from the validity of 88.3% (very decent), product practicality of 89% (efficient), and effectiveness of 83.42% (excellent). Thus, the media big book picture story is very decent, practical, and effective for learning speaking skills in kindergarten children